Does sagittal alignment influence outcome for patients who undergo anterior cervical fusion for degenerative pathologies? - Hélder Miguel Oliveira Henriques (2020)
Background: Cervical spine alignment parameters have been increasingly reported in the literature and clinical practice, particularly in deformity patients. However, whether they have an impact on outcomes in non-deformity patients is still uncertain. Objective: The objective of this study was to compare self-reported assessment of patients' clinical postoperative condition 12 months after one-level anterior cervical discectomy and fusion (ACDF) with radiological data. Methods: All patients who underwent one level ACDF in a single-center from 2016 to 2018 were included. The Health-Related Quality-of Life (HRQOL) scores involved Neck Disability Index (NDI), EuroQol Five Dimension Questionnaire (EQ-5D) and Core Outcome Measures Index (COMI) and were collected pre and post-operatively. Radiographic measurements included C0-C2, C1-C2, and C2-C7 Cobb angles, C2 slope, T1 slope, C2-C7 sagittal vertical axis (SVA), cervical tilt and cranial tilt. Results: The studied population consisted of 84 patients with a mean age of 51.1 years. A multivariate regression analysis showed that C2-C7 SVA was correlated with T1 slope, C2-C7 Cobb angle and C0-C2 Cobb angle (R2 = .303). There was no correlation between NDI after surgery and C2-C7 SVA. Both postoperative COMI (r = -.314, p = .005) and NDI scores (r = -.279, p = .013) showed a significant negative correlation with C0-C2 Cobb angle. Higher C0C2 Cobb angles were associated with improvement in NDI scores (p < .01). Conclusion: C2-C7 SVA correlated as expected with other radiological parameters but was not associated with improvement of clinical outcomes in a cohort of non-deformity patients who underwent one-level ACDF. C0-C2 Cobb angle correlated with functional outcomes.